Blockchain trend in Croatia: a qualitative analysis of real sector - Fuzul, Ena; Juričić, Vedran (Polytechnica, 2021)
Blockchain technology has gained great interest during the last few years, presenting itself as a leading alternative to traditional systems. Through 2017 and 2018, the technology went through an unstable period that manifested in various financial oscillations which left consequences on the further development of the technology. In order to understand the current state of the trend in Croatia, qualitative research on the real sector was conducted. The participants are Croatian companies operating in the field of blockchain, which, based on real experience, provide answers on various aspects of technology and suggestions for more successful further development within Croatia. The real sector perceives blockchain technology in Croatia as a technology with stable growth but suggests education, stronger connections with state institutions, and better legal regulation. The real sector believes that the future of blockchain technology in Croatia is optimistic and that technology is on the right path to its optimal development.